EFL University Students’ Difficulties in the Essay Writing Process - Maslihatul Bisriyah (Scope : Journal of English Language Teaching, 2022)
Research on foreign language writing has shown that most EFL students faced some difficulties to produce a good composition in English. However, attention has mainly been directed to explore errors found on students’ written work. Little is known about what difficulties students have in the writing process. The present study investigates difficulties students faced in the six steps of writing process, namely choosing a topic, gathering ideas, outlining or organizing ideas, writing the first draft, reviewing the content and structure, as well as revising and making final correction. This study applied a qualitative method by using questionnaire and interview to collect the data. The subjects were English Language Education students who were taking an Essay Writing course in the third semester. The findings indicate that students face difficulties in all steps of essay writing process. Among those six steps, outlining and gathering ideas are claimed as the most effortful steps students have to pass. Writing the first draft and revising are the next two steps considered as challenging. Lastly, choosing a topic and reviewing content and structure are also demanding for small part of students. The difficulties students have and suggestions they propose are presented in this study. Those could be a basis for doing some improvements at institutional as well as individual level.